2010
DOI: 10.1038/mt.2010.52
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Clinical Trial of Intratumoral Application of TG1042 (Adenovirus-interferon-γ) in Patients With Advanced Cutaneous T-cell Lymphomas and Multilesional Cutaneous B-cell Lymphomas

Abstract: Cutaneous lymphomas (CLs) are a heterogeneous group of lymphoproliferative disorders that are manageable by immunotherapy. Twenty-one patients were enrolled in a prospective open-label, dose-escalation multicenter study evaluating the effects of repeated TG1042 [adenovirus-interferon (IFN)-gamma] intralesional injections in patients with primary CLs, of which 18 were of T-cell and 3 of B-cell type. Repeated intralesional therapy using TG1042 consistently results in local tumor regressions in about half of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…(11, 5157) Of these, adenoviral-vector delivery of interferon-gamma has shown significant response rates, with local tumor regression in 8 out of 15 patients with cutaneous lymphomas. (56) Additionally, this trial demonstrated systemic responses in 4 out of 15 patients, which highlights systemic distribution despite a regional intratumoral injection. Intratumoral oncolytic viral therapies have been evaluated in pancreatic and hepatocellular cancers with some increases in lymphocyte infiltration.…”
Section: Surgical Immune Interventionsmentioning
confidence: 64%
“…(11, 5157) Of these, adenoviral-vector delivery of interferon-gamma has shown significant response rates, with local tumor regression in 8 out of 15 patients with cutaneous lymphomas. (56) Additionally, this trial demonstrated systemic responses in 4 out of 15 patients, which highlights systemic distribution despite a regional intratumoral injection. Intratumoral oncolytic viral therapies have been evaluated in pancreatic and hepatocellular cancers with some increases in lymphocyte infiltration.…”
Section: Surgical Immune Interventionsmentioning
confidence: 64%
“…20,21,24,[26][27][28][29][30][39][40][41][42][43][44][45][46][47] We also noted that although intrapleural gene transfer was detectable, we saw it at the surface of the pleural tumors. We did not reach a maximally tolerated dose.…”
Section: Adtk In Mesotheliomamentioning
confidence: 67%
“…Considerable experimental data from our group and other investigators demonstrated that intratumoral IFN-γ gene transfer to achieve long-term, continuous locoregional exposure of IFN-γ is likely an appropriate approach for improving efficacy and reducing toxicity of IFN-γ [9,10,15,16,23,24]. In this study, we reported that adenovirus-mediated IFN-γ gene transfer (Ad-IFNγ) inhibited tumor growth of human nasopharyngeal carcinoma (NPC) cells (Figure 2 and Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical application of recombinant IFN-γ protein is hampered by its short half-life and significant side effects. IFN-γ Gene therapy can continuously produce and release therapeutic protein in local focus to overcome the obstacle of recombinant IFN-γ protein [9,10,15,16]. …”
Section: Introductionmentioning
confidence: 99%